(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Implantation failure can occur during any of the three stages of implantation. It can be classified into four main categories, altered endometrial receptivity, embryonic defects, abnormal embryo-endometrial cross-talk and impairment in the regulation of immunologic mediators. Recurrent implantation failure needs a wide range of investigations. Several methods have been performed for RIF management but there is little consensus on the most effective one. Recently, some progress in treating RIF and thin endometrium has been made with the use of the PRP. Its main idea in patients with previous ET failures is based on the regulation of expression of growth factors and cytokines in the endometrium.